2009
DOI: 10.1016/j.bpj.2008.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin Inactivates Myocardial Cytochrome c Oxidase in Rats: Cardioprotection by Mito-Q

Abstract: Doxorubicin (DOX) is used for treating various cancers. Its clinical use is, however, limited by its dose-limiting cardiomyopathy. The exact mechanism of DOX-induced cardiomyopathy still remains unknown. The goals were to investigate the molecular mechanism of DOX-induced cardiomyopathy and cardioprotection by mitoquinone (Mito-Q), a triphenylphosphonium-conjugated analog of coenzyme Q, using a rat model. Rats were treated with DOX, Mito-Q, and DOX plus Mito-Q for 12 weeks. The left ventricular function as mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(132 citation statements)
references
References 51 publications
4
127
0
1
Order By: Relevance
“…DOX also decreased myocardial mitochondrial complex I and II activities, as well as the activity of the glutathione peroxidase (GPX). This is consistent with studies suggesting a key role for mitochondrial dysfunction and reactive oxygen species generation in triggering the deleterious cascade of the DOX-induced cardiotoxicity (4,5,28,29). In addition to mitochondrial, NADPH oxidase-dependent ROS generation (particularly NOX2-dependent) also may contribute to DOX-induced cardiotoxicity (4,30).…”
Section: Discussionsupporting
confidence: 91%
“…DOX also decreased myocardial mitochondrial complex I and II activities, as well as the activity of the glutathione peroxidase (GPX). This is consistent with studies suggesting a key role for mitochondrial dysfunction and reactive oxygen species generation in triggering the deleterious cascade of the DOX-induced cardiotoxicity (4,5,28,29). In addition to mitochondrial, NADPH oxidase-dependent ROS generation (particularly NOX2-dependent) also may contribute to DOX-induced cardiotoxicity (4,30).…”
Section: Discussionsupporting
confidence: 91%
“…Singal et al (1997) demonstrated that both increasing oxidant and decreasing antioxidant play a key role in ADR-induced cardiotoxicity. Antioxidant enzymes such as catalase (Chandran et al 2009) and rapidly inactivated GPx1 (Simmons and Jamall 1989) have been reported to be less expressed or have lower activity in cardiac tissue. Therefore, cardiac tissue is very vulnerable for oxidative stress damage.…”
Section: Discussionmentioning
confidence: 99%
“…To extend the potential translational implications of Trpm2 protection of the heart, we used a second model of cardiac injury: doxorubicin-induced cardiomyopathy (16), a model that involves oxygen free radicals (37) via Doxo's effects on mitochondrial electron transport chain (7,15). Survival of gKO mice treated with Doxo was much worse than WT mice treated similarly (Fig.…”
Section: Trpm2 Improved Survival and Limited Doxorubicin-induced Cardmentioning
confidence: 99%